2018
DOI: 10.1007/s11626-018-0270-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage time and nutrient medium on recovery of fibroblast-like cells from refrigerated collared peccary (Pecari tajacu Linnaeus, 1758) skin

Abstract: Animal cloning is a promising technology for biodiversity conservation, and its success depends on the recovery of nucleus donor cells. Specifically for collared peccaries, found sometimes in regions that are difficult to access, the storage at 4-6°C of skin tissues would be an alternative for the conservation of genetic material. Therefore, we aimed to evaluate different storage periods and the presence of a nutrient medium at 4-6°C on the recovery of somatic cells from the skin of collared peccaries. To anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…In this sense, studies related to the conservation of the collared peccary have been intensified, especially aimed at improving the techniques related to the preservation of somatic samples. Using this study, we established a culture condition for explants derived from the skin of adult collared peccaries (Santos et al, 2016) and developed a protocol for cryopreservation (Borges et al, 2017(Borges et al, , 2018a(Borges et al, , 2018b) and refrigeration of these explants (Queiroz Neta et al, 2018). In order to conduct the cloning experiments on this species by a somatic cell nuclear transfer, as well as to produce induced pluripotent cells, it is necessary to establish properly characterized cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, studies related to the conservation of the collared peccary have been intensified, especially aimed at improving the techniques related to the preservation of somatic samples. Using this study, we established a culture condition for explants derived from the skin of adult collared peccaries (Santos et al, 2016) and developed a protocol for cryopreservation (Borges et al, 2017(Borges et al, , 2018a(Borges et al, , 2018b) and refrigeration of these explants (Queiroz Neta et al, 2018). In order to conduct the cloning experiments on this species by a somatic cell nuclear transfer, as well as to produce induced pluripotent cells, it is necessary to establish properly characterized cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The samples were fixed in 4% paraformaldehyde and processed for embedding in paraffin as described by Queiroz Neta et al () for morphometric analysis, cell quantification and distribution analysis. Sections of 5.0 µm thickness were stained with haematoxylin‐eosin.…”
Section: Methodsmentioning
confidence: 99%
“…Karyoplasts have been routinely cryopreserved by slow freezing (Sharma et al , 2018) using a combination of dimethyl sulfoxide (DMSO), FBS, and sucrose as the cryoprotectant, as observed with Iberian lynx ( Lynx pardinus , León-Quinto et al , 2014). Although it is more desirable to use a somatic cell bank after tissue culture, the absence of in vitro culture conditions sometimes makes these banks unfeasible, resulting in the immediate formation of the targets for those somatic tissues (Borges et al , 2017a,b; Queiroz Neta et al , 2018). The three somatic tissue conservation techniques used for wild animals are slow-freezing cryopreservation (Mestre-Citrinovitz et al , 2016), vitrification (Borges et al , 2018a,b), and cooling at 4–6°C (Queiroz Neta et al , 2018).…”
Section: Overview Of the Iscnt Technique And Its Limitationsmentioning
confidence: 99%
“…Although it is more desirable to use a somatic cell bank after tissue culture, the absence of in vitro culture conditions sometimes makes these banks unfeasible, resulting in the immediate formation of the targets for those somatic tissues (Borges et al , 2017a,b; Queiroz Neta et al , 2018). The three somatic tissue conservation techniques used for wild animals are slow-freezing cryopreservation (Mestre-Citrinovitz et al , 2016), vitrification (Borges et al , 2018a,b), and cooling at 4–6°C (Queiroz Neta et al , 2018). In collared peccaries, we compared two techniques of vitrification and we observed that solid-surface vitrification was found to be a more efficient method for vitrifying skin tissue when compared with direct vitrification in cryovials, probably due to tissues not being involved in large amounts of cryoprotectants before passing through a drastic change in temperature during the solid-surface vitrification (Borges et al , 2017b).…”
Section: Overview Of the Iscnt Technique And Its Limitationsmentioning
confidence: 99%